The Relation Between the Variation of Electrical Resistivity Values and Moisture of Soil at Baghdad University, Iraq - AL-Mahemmdi , Waleed D.; Al-Banna, Ahmed S.; AL-Menshed, Firas H. (Iraqi Journal of Science, 2023)
Six ERI profiles using Wenner Schlumberger array were carried out at Baghdad University (ALJadiriya campus) to investigate soil at two sites. The spacing between electrodes of four profiles surrounding the new building in the Campus at the first site is 1 m, and the profile length ranges from 50 to 90 m. In comparison, two across profiles in the garden to detect water seepage in the site. The inverted model of the studied profiles shows many high and low resistivity zone. The sedimentology and mineralogy of the soil samples analysis from a depth range of 15 to 100 cm from three pits confirm the high homogeneity of the soil in the studied site composed of (silt and clay). The low resistivity values coincided with the moisture and amount of vegetable and herbs growth. Therefore, the authors believe the main factor causing variation in the resistivity value in the study area is the moisture Factor.